Multi‐scale environmental filters and niche partitioning govern the distributions of riparian vegetation guilds. Issue 10 (12th October 2015) - Hough-Snee, Nate; Laub, Brian G.; Merritt, David M.; Long, A. Lexine; Nackley, Lloyd L.; Roper, Brett B.; Wheaton, Joseph M.
Abstract : Across landscapes, riparian plant communities assemble under varying levels of disturbance, environmental stress, and resource availability, leading to the development of distinct riparian life‐history guilds over evolutionary timescales. Identifying the environmental filters that exert selective pressures on specific riparian vegetation guilds is a critical step in setting baseline expectations for how riparian vegetation may respond to environmental conditions anticipated under future global change scenarios. In this study, we ask: (1) What riparian plant guilds exist across the interior Columbia and upper Missouri River basins? (2) What environmental filters shape riparian guild distributions? (3) How does resource partitioning among guilds influence guild distributions and co‐occurrence? Woody species composition was measured at 703 stream reaches and each species' morphological and functional attributes were extracted from a database in four categories: (1) life form, (2) persistence and growth, (3) reproduction, and (4) resource use. We clustered species into guilds by morphological characteristics and attributes related to environmental tolerances, modeling these guilds' distributions as a function of environmental filters—regional climate, watershed hydrogeomorphic characteristics, and stream channel form—and guild co‐existence. We identified five guilds: (1) a tall, deeply rooted, long‐lived, evergreen tree guild, (2) a xeric, disturbance tolerant shrub guild, (3) a hydrophytic, thicket‐forming shrub guild, (4) a low‐statured, shade‐tolerant, understory shrub guild, and (5) a flood tolerant, mesoriparian shrub guild. Guilds were most strongly discriminated by species' rooting depth, canopy height and potential to resprout and grow following biomass‐removing disturbance (e.g., flooding, fire). Hydro‐climatic variables, including precipitation, watershed area, water table depth, and channel form attributes reflective of hydrologic regime, were predictors of guilds whose life history strategies had affinity or aversion to flooding, drought, and fluvial disturbance. Biotic interactions excluded guilds with divergent life history strategies and/or allowed for the co‐occurrence of guilds that partition resources differently in the same environment. We conclude that the riparian guild framework provides insight into how disturbance and bioclimatic gradients shape riparian functional plant diversity across heterogeneous landscapes. Multiple environmental filters should be considered when the riparian response guild framework is to be used as a decision‐support tool framework across large spatial extents.